Profil Senyawa Fitokimia Menggunakan Metode FTIR dan Pengujian Nilai SPF Secara In Vitro Formulasi Lotion O/W Ekstrak Etanol 96% Daun Binahong Hijau - Nurluthfiana, Deby; Adiyas Putra, Teguh; Irawan, Ade (Universitas Borneo Lestari, 2025)
The 96% ethanol extract of green binahong leaves contains flavonoid compounds with potential activity as a sunscreen. Flavonoid compounds have been identified via FTIR and show part of this functional group. in the form of aliphatic C-H, C=O, C=C, and C-O. This research aims to determine the stability of the physical and chemical quality of o/w type sunscreen lotion and its activity as a sunscreen in vitro using a UV-vis spectrophotometer. The extract is obtained using the ethanol maceration method and then formulated into lotion and o/w cream and tested for physical and chemical stability and tested for SPF in vitro with a spectrophotometer. The results of this research indicate that the o/w lotion formula is stable during the storage period of 6 cycles. The increase in the diameter value of spreadability and sticking time is influenced by storage factors, the longer the preparation is stored, the viscosity will decrease. Sunscreen activity calculated using the Mansur equation shows that the SPF value at 0.5%, 2.5% and 4.5% levels of green binahong leaf extract is 3.37; 8.25 ; 8.93. The sunscreen lotion preparation of 96% ethanol extract of green binahong leaves is stable during storage and has activity as a sunscreen.